DEVELOPING A SUSTAINABLE CHILDRENSWEAR SIZING SYSTEM : BODY SIZE, SILHOUETTE SHAPE AND CLOTHING KEY DIMENSIONS - Marzie Hatef, Jali; Musdi, Shanat (Jomard Publishing, 2022)
Inconsistent children's garment sizing may cause fit issues, leaving youngsters unable to find clothing in the correct size or recognise what size fits their body form. This research attempts to find sustainable solutions to design issues regarding non-fitting children's clothing that involve reducing postconsumer waste. Through this concept, children’s clothing can be customised based on the garment type, as well as the child’s body features and silhouette. By employing the patternmaking system M. Müller & Sohn technique, patterns were created using Computer-Aided Design to enhance flat patterns of basic silhouettes. Patterns were developed and used to dress virtual mannequins with CLO3D, a threedimensional virtual sewing and try-on software. CLO3D system realizes virtual fitting, including threedimensional body modeling and a three-dimensional virtual sewing fitting map. According to the international size charts, the findings of this study demonstrate that different silhouette shapes often do not follow regular market sizes, while children’s sizes can be recognised effectively by understanding their body size, age, height, and weight. Therefore, children’s clothing can be customised with a specific height range, body size and silhouette shape. Henceforth, when designing and purchasing children’s clothes, accurate information could prevent the growth in post-consumer waste arising from the production of children’s clothing and be an essential step to achieving sustainability in the apparel industry.